Al-Muqobalah in the Qur'an; Analyst of Surah An-Naziat - Fadhlan Habibi Harahap; Abdul Hafidz Zaid (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to explain al-muqobalah in the science of al-badi' to determine its types, how it is applied in Surah An-Naziat, and to uncover the secrets of the verses that use al-muqobalah. This research is a library research that utilizes primary and secondary sources related to the research object. Al-Muqobalah is the act of mentioning something with its equivalent in some attributes or with differences in other attributes. Al-Muqobalah has several types, including those related to quantity, words, meanings, order, and differences in words. The use of al-muqobalah in the Quran reveals certain secrets. The application of al-muqobalah in Surah An-Naziat is highly beneficial for unveiling the broader secrets and meanings contained in the Surah, especially since it addresses topics related to the Day of Judgment or ghaibiyyat. This enhances its impact on the reader's heart.